John Lach's practical philosophy - Skowroński, Krzysztof Piotr. (Value Inquiry Book Series, 2018)
John Lachs (1934-) has been one of the most interesting American philosophers for nearly sixty years. His philosophical, educational, and public activity has been an attempt to show the relevance of philosophy to life. This is the first book dedicated to his thought. International scholars have proposed different themes in Lachs' philosophy, so as to present its enormous potential. Lachs' responses to his critics shows that dialogue with his critics is an inspirational activity for both sides. Lachs' way of philosophizing can be seen as exemplary for those who want to unify and present a clear and understandable articulation of moral and philosophical messages to everyone.